Effects of semi-deep water irrigation on hybrid indica rice lodging resistance - Gao, Hui; Dou, Zhi; Chen, Linrong; Lu, Yao; Sun, Dong; Xu, Qiang; Sun, Ruyin; Chen, Xueying (Frontiers in Plant Science, 2022)
Recently, area of rice-aquatic animal integrated farming (RAAIF) enlarged rapidly in China as its favorable benefit and lower application of pesticide and fertilizer. However, rice lodging occurred frequently under RAAIF, which restricted rice yield. We assumed that semi-deep water irrigation may cause weaker rice lodging resistance since it is the most significant environmental factor for RAAIF that distinguished from rice monoculture. To investigate the response of rice stem lodging resistance to semi-deep water irrigation and its mechanism, three irrigation management modes, including the typical high-yield irrigation model that mainly based on swallow and wetting (CK), semi-deep water irrigation from late tillering stage to jointing stage (SDI1), semi-deep water irrigation from jointing stage to middle grain-filling stage (SDI2), were conducted using three hybrid indica rice varieties, Shenliangyou136 (SLY136), Huiliangyousimiao (HLYSM) and Wanxiangyou982 (WXY982). Mechanics analysis indicated that bending moment by whole plant (WP) and breaking strength (M) were both decreased by semi-deep water irrigation when compared with CK, while M presented a larger decreasing amplitude than WP, which induced increased lodging index (LI) of rice, for all the tested varieties. SLY136 and HLYSM was affected more largely by SDI1 while WXY982 was affected more strongly by SDI2. Significant weaker breaking force under two semi-deep water irrigation modes contributed to the decreased M relative to CK. Morphology results showed that semi-deep water irrigation thinned mechanical tissue, sclerenchyma cell and parenchymal cell, and reduced the number of vascular bundles and caused more loose arrangement, inducing the lower fullness of rice basal internode. Decreased accumulation of lignin and cellulose were also linked to the weaker breaking force of basal internode under semi-deep water irrigation, which was verified by correlation analysis. WXY982 had obvious lower structural carbohydrates content under semi-deep water irrigation than the other two varieties and thus showed worse breaking force and LI. In conclusion, the worse mechanical strength of rice basal internode under semi-deep water irrigation was closely associated with weaker vascular bundle development and suppressed structural carbohydrate accumulation, and the decreasing degree of lodging resistance varied between rice varieties and semi-deep water irrigation periods.